Mechanical and durability assessment of concrete containing seashells: A review. Issue 1 (1st January 2021) - Bamigboye, Gideon; Enabulele, David; Odetoyan, Abimbola O.; Kareem, Mutiu A.; Nworgu, Austin; Bassey, Daniel
Abstract: This study reviews recent literature on the mechanical and durability properties of concrete incorporating seashells as partial or full substitutes for conventional materials. The study summarizes various contributions elucidating the various waste seashells utilized, the growing worldwide aquaculture production, seashell material preparation and treatment, chemical composition, physical properties, and different mechanical and durability test methods adopted by previous studies such as compressive strength, split tensile strength, flexural strength, modulus of elasticity, freeze-thaw resistance, water permeability, air content, chemical attack, carbonation, and weight loss. The study showed that mechanical properties indicate reductions of different percentages with increases in substitution ratio at 5% to 75%, compared to control mixes. However, relative increases in mechanical strength were recorded with the increase in curing age up to 90 days. Influence of seashells on durability properties varied across various durability tests at different seashell percentages. In a nutshell, the use of seashells in concrete production has a good effect, and further innovative research can solidify its utilization in the drive towards sustainable development.